The Effect of Environmental Costs, Governance Risk Compliance (GRC) on Financial Performance with Company Size as Moderating Variable - Putri, Ni Wayan Remita Karisma; Sri Werastuti, Desak Nyoman; Yuniarta, Gede Adi (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Financial performance measurement is crucial in assessing a company's success. A company's financial performance must be continuously monitored year after year. This study aims to examine and analyze the influence of environmental costs and GRC on financial performance, with company size as a moderating variable. This study employed a quantitative method with Moderated Regression Analysis (MRA) as the data analysis technique. This study was conducted on companies in the Energy and Basic Materials Industry sectors listed on the Indonesia Stock Exchange (IDX) consecutively during the 2021-2023 period. The sampling technique used was purposive sampling, with a total sample size of 39 companies. The results show that environmental costs have a significant and positive effect on financial performance, GRC has a significant and positive effect on financial performance, company size can moderate or strengthen the effect of environmental costs on financial performance, and company size moderates or strengthens the effect of GRC on financial performance. These results indicate that disclosure of environmental costs and GRC can improve a company's financial performance, with company size as a moderating variable.